The smallest biggest theropod dinosaur: a tiny pedal ungual of a juvenile Spinosaurus from the Cretaceous of Morocco - Maganuco, Simone; Dal Sasso, Cristiano (PeerJ, 2018)
We describe a nearly complete pedal ungual phalanx, discovered in the Kem Kem Beds (Cenomanian) of Tafilalt region, south-eastern Morocco. The bone is symmetric, pointed, low, elongate, and almost flat ventrally in lateral aspect. This peculiar morphology allows to refer the specimen to the smallest known individual of the genus Spinosaurus. The bone belongs to an early juvenile individual and it is proportionally identical to the ungual of the third digit of a large partial skeleton recently found, suggesting an isometric growth for this part of the pes and the retention of peculiar locomotor adaptations—such as traversing soft substrates or paddling—during the entire lifespan.
Keywords: Spinosaurus; Cenomanian; Theropoda; Pedal ungual; Morocco